Resonate : present visual stories that transform audiences - Duarte, Nancy (Hoboken, N.J. : John Wiley & Sons, 2010)
Reveals the underlying story form of all great presentations that will not only create impact, but will move people to action Presentations are meant to inform, inspire, and persuade audiences. So why then do so many audiences leave feeling like they've wasted their time? All too often, presentations don't resonate with the audience and move them to transformative action. Just as the author's first book helped presenters become visual communicators, Resonate helps you make a strong connection with your audience and lead them to purposeful action. The author's approach is simple: building a presentation today is a bit like writing a documentary. Using this approach, you'll convey your content with passion, persuasion, and impact. Author has a proven track record, including having created the slides in Al Gore's Oscar-winning An Inconvenient Truth; Focuses on content development methodologies that are not only fundamental but will move people to action; Upends the usual paradigm by making the audience the hero and the presenter the mentor; Shows how to use story techniques of conflict and resolution. Presentations don't have to be boring ordeals. You can make them fun, exciting, and full of meaning. Leave your audiences energized and ready to take action with Resonate
Why resonate? -- Lessons from myths and movies -- Get to know the hero -- Define the journey -- Create meaningful content -- Structure reveals insights -- Deliver something they'll always remember -- There's always room to improve -- Change your world -- Inspiration is everywhere.
Includes bibliographical references (p. 234-236) and index.
Keywords: Business presentations; Comunicación empresarial; Presentaciones comerciales